Error Analysis of Subject-Verb Agreement on Students’ Essay Writing of Grade VIII at SMP Negeri 1 Sidamanik - Lastri Wahyuni Manurung; Hujaefa HI. Muhammad; Godwill Chenyuei Akwene (Jurnal Scientia, 2022)
The research was done to find out the types of errors students make in writing an essay and to explore how the errors happened in their writing. The data were analyzed by identifying the errors that students made in their writing focused on subject-verb agreement and tenses, then classifying the sources of errors based on Krashen’s theory which classifies them into addition, ordering, misinformation and deletion. This theory was used to analyze the data in this research. This study analyzed the errors found in students' grade VIII writing at SMP Negeri 1 Sidamanik. The findings of this study also show that the number of errors made by the students in their writing is in line with the results of the previous studies. The 186 errors in subject-verb agreement and tense out of 473 total clauses have proven those studies. The errors that students made when they were writing compositions were found not only in subject-verb agreement and tenses but also in spelling, word order, capitalization, article, word choice, the use of pronouns, and other errors that are usually found in writing. Error found on subject-verb agreement, there is 24.19 percent of misinformation errors. It is found there is 1.6 percent of ordering errors, deletion errors found at 19.34 percent, 3.22 percent of addition errors on the data analysis. Obviously proves that writing as one of the skills in English is still being faced as one of the most difficult subjects to be mastered. It occurs since writing is viewed as a complex process even in the first language. It means, students do not only face difficulties when they are writing an essay in a second or foreign language but they also face the same difficulties when they are writing in their own native language.